Synthesis, biological evaluation, and molecular docking of new series of antitumor and apoptosis inducers designed as VEGFR-2 inhibitors - Abdallah E. Abdallah; Reda R. Mabrouk; Maged Mohammed Saleh Al Ward; Sally I. Eissa; Eslam B. Elkaeed; Ahmed B. M. Mehany; Mariam A. Abo-Saif; Ola A. El-Feky; Mohamed S. Alesawy; Mohamed Ayman El-Zahabi (Taylor & Francis Group, 2022)
Based on quinazoline, quinoxaline, and nitrobenzene scaffolds and on pharmacophoric features of VEGFR-2 inhibitors, 17 novel compounds were designed and synthesised. VEGFR-2 IC50 values ranged from 60.00 to 123.85 nM for the new derivatives compared to 54.00 nM for sorafenib. Compounds 15a, 15b, and 15d showed IC50 from 17.39 to 47.10 µM against human cancer cell lines; hepatocellular carcinoma (HepG2), prostate cancer (PC3), and breast cancer (MCF-7). Meanwhile, the first in terms of VEGFR-2 inhibition was compound 15d which came second with regard to antitumor assay with IC50 = 24.10, 40.90, and 33.40 µM against aforementioned cell lines, respectively. Furthermore, Compound 15d increased apoptosis rate of HepG2 from 1.20 to 12.46% as it significantly increased levels of Caspase-3, BAX, and P53 from 49.6274, 40.62, and 42.84 to 561.427, 395.04, and 415.027 pg/mL, respectively. Moreover, 15d showed IC50 of 253 and 381 nM against HER2 and FGFR, respectively.